Impact of Corporate Governance on Firm Value of Nepalese Insurance Companies - Mishra, Akalesh Kumar; Chaturbedi, Dhananjay; Kshatry, Manisha; Bhatta, Sushmita; Pradhan, Sumit (Nepalese Journal of Business, 2025)
The study examines the impact of corporate governance on firm value of Nepalese insurance companies. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are board size, board meetings, independent directors, audit committee, firm size, and firm age. The study is based on secondary data of 15 Nepalese insurance companies with 105 observations for the period from 2016/17 to 2022/23. The data were collected from Insurance Statistics published by Insurance Board of Nepal and annual reports of the selected insurance companies. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on firm value of Nepalese insurance companies. The study showed that board size has a positive impact on return on assets and return on equity. It indicates that increase in board size leads to increase in return on assets and return on equity. Similarly, board meetings have a positive impact on return on assets and return on equity. It indicates that increase in board meetings lead to increase in return on assets and return on equity. Likewise, independent directors have a negative impact on return on assets and return on equity. It indicates that presence of independent directors lead to decrease in return on assets and return on equity. In addition, audit committee has a positive impact on return on assets and return on equity. It indicates that increase in audit committee member leads to increase in return on assets and return on equity. Further, the study also showed that firm size has a positive impact on return on assets and return on equity. It indicates that increase in firm size leads to increase in return on assets and return on equity. In addition, firm age has a positive impact on return on assets and return on equity. It indicates that older the firms, higher would be the return on assets and return on equity.